Cronologiá de la ocupación humana en los canales septentrionales de Patagonia occidental, Chile - Reyes, Omar; Méndez, César; San Roman Bontes, Manuel Julio (My University, 2019)
CHRONOLOGY OF THE HUMAN OCCUPATION OF THE NORTHERN WATER COURSES OF WESTERN PATAGONIAN, CHILE. A systematic radiocarbon dating program in the Chonos Archipelago in the northwestern channels of Patagonia has enabled a better understanding of the occupation of this area by marine hunter-gatherers. The temporal distribution and the population dynamics of these occupations are evaluated by using chronological information to understand human activity across the landscape. Samples were obtained from a variety of archaeological sites spanning the last 6200 years. These include dates from strata buried beneath organic soils, rock shelters, individual burials and ossuaries, and open-air shell middens, some of which were formed by recent shellfish harvesting. Both the evidence of the initial occupation of this territory, as well as the continuity or discontinuity in its use over time, are discussed. The intensity of the human chronological signature starting during the Mid-Holocene and continuing until recent times is evaluated and possible explanations for the (dis)continuities in the use of the archipelagic space are discussed.
Keywords: maritime hunter-gatherers; mid and late holocene; radiocarbon chronology; western patagonian channels